Gender Differences in the Distribution of Creativity Scores: Domain-Specific Patterns in Divergent Thinking and Creative Problem Solving - He, Wu-jing; Wong, Wan-chi (Frontiers in Psychology, 2021)
The present study examined gender differences in the distribution of creative abilities through the lens of the greater male variability hypothesis, which postulated that men showed greater interindividual variability than women in both physical and psychological attributes (Ellis, 1894/1934). Two hundred and six (51.9% female) undergraduate students in Hong Kong completed two creativity measures that evaluated different aspects of creativity, including: (a) a divergent thinking test that aimed to assess idea generation and (b) a creative problem-solving test that aimed to assess restructuring ability. The present findings extended the research of greater male variability in creativity by showing that men generally exhibited greater variance than women in the overall distribution of the creativity scores in both divergent thinking and creative problem solving, despite trivial gender differences in mean scores. The findings further enriched the discourse of the greater male variability hypothesis by showing interesting domain-specific gendered patterns: (1) greater male variability was more likely to occur in figural forms of creativity, with larger effect sizes, when compared to the variability in verbal forms of creativity; and (2) mixed gendered patterns were found in the upper tails of the creativity score distribution with respect to the verbal domain but not the figural one, despite greater male representation being consistently observed in the lower tail of the distribution. Possible underlying mechanisms and implications were discussed.